(untitled) (Journal of Psychiatrists’ Association of Nepal, 2025)
Background: The COVID-19 pandemic has been associated with significant social and internalized stigma, particularly in low-resource settings. Yet, few studies have examined its psychological impact. This study aims to (1) find out the levels of COVID-19-related internalized stigma among confirmed COVID-19 cases and suspects in Nepal, (2) compare their scores and scores of anxiety and depressive symptoms between the two groups, and (3) find the associations of scores anxiety, and depressive symptoms with COVID-19-related internalized stigma in both groups. Methods: It was a cross-sectional study conducted during the first wave (July–November 2020) in five health facilities in two provinces of Nepal, with 306 COVID-19 cases and 89 suspects. A semi-structured questionnaire, adapted Internalized Stigma of Mental Illness scale, and Hospital Anxiety and Depression Scale were administered. Descriptive and correlation analyses were used to compare the two groups. Results: COVID-19 cases reported significantly more high COVID-19-related internalized stigma (25.2% cases, 3.4% suspects) (p<0.001) than the suspects. Cases reported significantly higher anxiety (28.1% vs. 6.7%) (p < 0.001) and depressive symptoms (38.9% vs. 12.4%) (*p* <0.001) than suspects. Among cases, anxiety and depressive symptoms correlated with COVID-19-related internalized stigma score (p=0.001; p<0.001) and four subdomains- alienation (p<0.001; p<0.001), stereotype endorsement (p<0.001; p<0.001), discrimination experience (p<0.001; p<0.001), social withdrawal (p<0.001; p<0.001). Whereas among the COVID-19 suspects, only social withdrawal (p=0.001) and stigma resistance (p<0.05) correlated with anxiety symptoms and there were no correlations with depressive symptoms. Conclusion: The findings highlight the disproportionate psychological burden on COVID-19 cases, driven by internalized stigma related to the illness. Targeted mental health interventions are needed to mitigate the impact of stigma with attention to differences between cases and suspects.